Effect of storage temperature and produce type on the survival or growth of Listeria monocytogenes on peeled rinds and fresh-cut produce - Moreira, Juan; Mera, Erika; Singh Chhetri, Vijay; King, Joan M.; Gentimis, Thanos; Adhikari, Achyut (Frontiers in Microbiology, 2023)
Whole and fresh-cut produce are minimally processed and susceptible to microbial contamination. This study evaluated the survival or growth of L. monocytogenes on peeled rinds, and fresh-cut produce at different storage temperatures. Fresh-cut fruits and vegetables, including cantaloupe, watermelon, pear, papaya, pineapple, broccoli, cauliflower, lettuce, bell pepper, and kale (25 g pieces) were spot inoculated with 4 log CFU/g of L. monocytogenes and stored at 4 or 13°C for 6 days. Cantaloupe and bell pepper rind disks (20 cm2), mimicking whole produce were inoculated with low inoculum level (4 log CFU/mL) and high inoculum level (6 log CFU/mL) and stored at 24°C up to 8 days and 4°C up to 14 days, respectively. L. monocytogenes counts on fresh-cut pear samples stored at 4°C increased significantly by 0.27 log CFU/g. However, Listeria levels on kale (day 4), cauliflower (day 6), and broccoli (day 2) were significantly reduced by 0.73, 1.18, and 0.80 log CFU/g, respectively, at 4°C. At 13°C, the bacterial counts increased significantly after a day of storage on fresh-cut watermelons (increasing by 1.10 log CFU/g) and cantaloupes (increasing by 1.52 log CFU/g). Similar increases were observed on pears (1.00 log CFU/g), papayas (1.65 log CFU/g), and green bell peppers (1.72 log CFU/g). Pineapple samples did not support the growth of L. monocytogenes at 13°C with a significant reduction of 1.80 log CFU/g by day 6. L. monocytogenes levels significantly increased in fresh-cut lettuce at 13°C but remained stable on kale, cauliflower, and broccoli after 6 days of storage. Stable population was observed also on cantaloupe rinds up to 8 days at 24°C. While on the outer surface of bell peppers, the population level decreased below the detectable limit of the test (10 CFU/20 cm2) after 14 days of storage at 4°C. The results demonstrated variable survival behavior of L. monocytogenes on fresh-cut produce with produce type and storage temperature.